Confronting violence : a manual for Commonwealth action (Commonwealth Secretariat LondonGB, 1987)
Defines and surveys extent of domestic violence in Commonwealth countries and examines the legal approaches used to provide assistance for victims of abuse. Makes a critical analysis of these approaches and suggests strategies for their development. Surveys the current legal approaches used to confront sexual assault and sexual harassment. Discusses prosecution of rape and methods that can be employed to ameliorate situation of women confronted with sexual harassment. Contains example of Canadian sexual assault kit used in investigation of sexual assault crimes and recommendations of multi-disciplinary expert group on violence against women.
IDS